Public Policies for Agricultural Diversification: Implications for Gender Equity - Valencia, Vivian; Wittman, Hannah; Jones, Andrew D.; Blesh, Jennifer (Frontiers in Sustainable Food Systems, 2021)
Gender equity is recognized as central to sustainable development, but women still face significant constraints in accessing and controlling productive resources important for agricultural livelihoods. Identifying mechanisms (e.g., policies and interventions) in agriculture that enhance women's empowerment—a critical aspect of gender equity—is of paramount importance for sustainable development. In this study, we investigate how Brazil's flagship targeted public food procurement program, the National School Feeding Program (PNAE), influences women's empowerment in southern Brazil. We conducted household surveys on farm characteristics and practices, women's empowerment (e.g., participation in farm decision-making and control over income), and women's participation in social movements, with farmers (n = 75) who do and do not participate in the PNAE. We found that women were more empowered in households participating in the PNAE, and that this empowerment was associated with diversified farming systems. When women had greater levels of participation in farm management decisions, agrobiodiversity and use of agroecological practices were higher. We also show that women's participation in agroecological social movements was associated with significantly higher empowerment (both in control over income and greater participation in decision-making). This study identifies targeted public food procurement as a promising policy instrument with potential to link cross-sectoral Sustainable Development Goals (SDGs) to sustainably increase food production (SDG 2), provide economic opportunities for small-scale farmers (SDG 1), and create an economic space that women in agriculture can more easily access (SDG 5).